Gut microbiota modulates lung gene expression and metabolism to aid SD rats in adapting to low-pressure hypoxia - Zheng Chen; Shatuo Chai; Yuxia Ding; Kaiyue Pang; Tanqin Dong; Dongwen Dai; Jianmei Wang; Shuxiang Wang; Shujie Liu (Microbiology Spectrum)
ABSTRACT Hypoxia has long posed a serious threat to the health of both animals and humans, causing respiratory acidosis, metabolic disorders, systemic inflammation, oxidative stress damage, and other issues, thereby endangering life and limiting development in high-altitude areas. Gut microbiota plays a crucial role in life activities and hypoxia adaptation. We transplanted the gut microbiota from small mammals, plateau zokors (Myospalax baileyi), from the Qinghai–Tibetan plateau (3,500 m) to Sprague–Dawley (SD) rats housed in a hypobaric chamber (equivalent to 6,000 m altitude) for 30 days. The results showed that microbiota transplantation significantly reshaped the gut microbiota structure of the rats, notably increasing the abundance of short-chain fatty acid-producing bacteria Lachnospiraceae and Prevotellaceae, alleviating hypoxia and acidosis, reducing pulmonary hypertension and right ventricular hypertrophy, increasing the production of anti-inflammatory substances like indole-3-lactic acid, and reducing the generation of pro-inflammatory substances, such as histamine and uric acid. It also decreased the expression of inflammatory genes like lgE, TNFα, and IFN-γ in the lung. Fecal microbiota transplantation from plateau-specific species to low-altitude SD rats effectively altered metabolism, changed gene expression, decreased pulmonary artery pressure, and enhanced plateau adaptability. This study demonstrates the potential effectiveness of treating hypoxic pulmonary hypertension through microbiota transplantation and offers insights into improving hypoxia adaptation.IMPORTANCEWe report the beneficial effects of FMT on respiratory capacity, lung metabolism, and lung gene expression in SD rats under hypoxic conditions. We revealed the inhibitory effects of gut microbiota on lung mast cells and histamine expression under hypoxic conditions. The study demonstrated the potential effectiveness of treating HPH through FMT and offers insights into improving hypoxia adaptation.